Effect of Work Supervision and Discipline on Employee Performance: Study on A Manufacturing Company in Bandung City - Kiki Andang P; Aan Hardiyana (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2021)
This study aimed to determine the effect of supervision and work discipline on employee performance. This research method uses a quantitative approach with multiple regression analysis. The source of this research uses primary data. This research data collection using a questionnaire. The sample of this research is 57 employees using the saturated sampling technique. The results of this study indicate that partially and simultaneously, there is a significant influence between the variables of supervision and work discipline on employee performance, where supervision and work discipline have a simultaneous effect of 58.8% on employee performance. At the same time, the remaining 41.2% were influenced by other factors not observed in this study. Recommendations for performance the supervision carried out can be hiring human resources following the qualifications. Furthermore, preferably implementing a reward and punishment system for those who have a good or inadequate level of work discipline, pay attention to the level of employee attendance, establish rules, and strict legal sanctions.